Kajian Elemen Penciri Shukubamachi (Kota Persinggahan) di Jalur Tōkaidō, Jepang Abad XVII - Subangun, Radiaswari (ATRIUM: Jurnal Arsitektur, 2025)
Title: Study of Typical Elements of Shukubamachi’s (Post Towns) in the Tōkaidō Route, 17th-century Japan A town, as a physical environment, has various dimensions of value that reflect its characteristics. Both in terms of historical value and other factual aspects of building the town’s identity. Shukubamachi is a unique type of town that developed from political policies established by the Tokugawa shogunate in 17th-century Japan, during the Edo period (1603-1868), a two-decade period of peace. This study investigates significant elements of the shukubamachi. This research employs a qualitative descriptive method, systematically compiling a detailed description of shukubamachi’s phenomenon based on observations obtained from historical documentation and visual illustrations. The final result can be concluded that the characteristics of the shukubamachi are identified by the presence of three main functional elements: the honjin, the waki-honjin, and the ton’yaba. In addition to the transit facilities provided for the bakufu government, there were other functions initiated by the locals, such as public lodging with additional bathhouses and restaurants (hotago-ya), simple lodging (kichin-yado), supply stores (shouka), and tea houses (chaya).